Knowledge regarding endotracheal suctioning among Nurses of a teaching hospital of Kaski District - Lamichhane, Anju; Koirala, Dipti; Thapa, Bindu; Silwal, Muna (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Endotracheal suctioning (ETS) is an essential procedure that involves removal of accumulated lung secretions from tracheobronchial tree through an artificial airway. It is crucial that this procedure is performed with professional competence based on updated scientific evidence and guidelines that guarantee efficiency and safety of the patient to prevent the common infection like ventilator associated pneumonia (VAP).Objectives: To identify the level of knowledge regarding ETS among nurses and to measure the association between knowledge level and selected demographic variables.Methods: Descriptive cross-sectional research design was adopted for this study which was conducted in Gandaki Medical College Teaching Hospital and Research Centre of Kaski, Nepal. The study population were all the nurses working in in-patient department of the hospital. Sample size was calculated through standard formula and probability simple random sampling technique was used to select 92 nurses. Semi- structured self-administered questionnaire was used to collect data. Collected data was entered, coded and edited into Statistical Package for Social Science (SPSS) version 16. Data was analyzed by employing both descriptive and inferential statistical methods.Result: Only 4.3% of the total respondents had good knowledge on ETS whereas 52.2% had fair knowledge and 43.5% had poor knowledge. There was significant association between respondent’s level of knowledge on ETS and ethnicity (p=0.049) and professional qualification (p=0.028).Conclusion: Nearly half of the nurses had poor knowledge on ETS. Therefore, it is necessary to upgrade nurse’s knowledge on ETS through inservice education programs.